DEVELOPMENT OF PHYSICS TEST INSTRUMENTS TO MEASURE PROBLEM SOLVING SKILL IN CLASS XI SMA - Nadiya Saqinah; Yuni Warty (EDUTECH, 2024)
This study aims to determine the problem-solving abilities of students with statis fluid material. The type of research used is RD with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted at SMA Swasta Persiapan 2 Padang Tualang in class XI, which amounted to 15 students for the small-scale test and 35 students for the large-scale test. The results of the study were obtained based on the results of validation by experts on three aspects of assessment, namely construct, material, and language, which obtained an average value of 95.8% with a very valid category. In the small-scale test, students’ problem-solving ability obtained an average score of 34.00 with a lower category, whereas in the large scale tets, students obtained an average of 59.00 with a lower category. So, it can be concluded that the test instrument developed can measure and improve students’ problem-solving skills.